PENGARUH PEMBERIAN BEBERAPA DOSIS PUPUK KOMPOS (GREENBOTANE)TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT ( ELAEIS QUIENEENSIS JACQ) DI PEMBIBITAN UTAMA - Andri, Raby Kurniawan; Wawan, Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the influence and dosage of compost fertilizer (Greenbotane) which produces the best growth of palm seedlings.Penelitian conducted in Experimental Garden Faculty of Agriculture University of Riau. Type of land used is Mineral Acid. The research was conducted for four months starting from August to December 2016. The research was conducted experimentally using Randomized Complete Random Design (RAL), which consisted of 5 treatments with 4 replicates. The total experimental unit amounted to 20 plots, in which each plot contained 2 plants . The observed data were analyzed statistically by using Analysis of Varian (ANOVA), then continued by the Multiple Range Test of Duncan at 5% level. The observed parameters consist of plant height, number of leaves, diameter of stump, wet weight of plant, dry weight and root canopy ratio. The results show that compost fertilizer (Greenbotane) treatment can increase plant height, cobweb diameter, wet weight and dry weight of plant. The best treatment for oil palm crop is fertilizer application (Greenbotane) with dose 200g / polybag.Keywords: Greenbotane compost, palm oil